2021
DOI: 10.1128/mbio.02392-21
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of the Salmonella FliE Protein That Forms the Base of the Flagellar Axial Structure

Abstract: The FliE component of the bacterial flagellum is the first protein secreted through the flagellar type III secretion system (fT3SS) that is capable of self-assembly into the growing bacterial organelle. The FliE protein plays dual roles in the assembly of the Salmonella flagellum as the final component of the flagellar type III secretion system (fT3SS) and as an adaptor protein that anchors the rod (drive shaft) of the flagellar motor to the membrane-imbedded MS-ring structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
0
14
0
1
Order By: Relevance
“…We have previously shown that the retained flagellar type III secretion system (FT3SS) is functional in nonflagellated Lysobacter enzymogenes OH11 so that the hook-capping protein FlgD is secreted into the culture media ( 48 ). It has been reported that FliE is the first export substrate secreted by the FT3SS ( 63 ) and that interactions of FliE with FliP and FliR, which are export gate proteins of the FT3SS, fully open the exit gate of the protein export channel in the FT3SS, allowing other flagellar building blocks to diffuse down the central channel of the growing flagellar structure ( 64 ). Assuming that certain positive regulators, which may be under the control of FleQ derived from Xanthomonas oryzae (Xo-FleQ) and facilitate the production of an antifungal weapon (HSAF) by the OH11 strain, may be secreted via the FT3SS, it is speculated that the expression of Xanthomonas oryzae FliE (Xo-FliE) would fully open the export channel of the FT3SS through interactions of Xo-FliE with FliP and FliR, allowing the positive regulators to exit the cell and suppressing HSAF production.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that the retained flagellar type III secretion system (FT3SS) is functional in nonflagellated Lysobacter enzymogenes OH11 so that the hook-capping protein FlgD is secreted into the culture media ( 48 ). It has been reported that FliE is the first export substrate secreted by the FT3SS ( 63 ) and that interactions of FliE with FliP and FliR, which are export gate proteins of the FT3SS, fully open the exit gate of the protein export channel in the FT3SS, allowing other flagellar building blocks to diffuse down the central channel of the growing flagellar structure ( 64 ). Assuming that certain positive regulators, which may be under the control of FleQ derived from Xanthomonas oryzae (Xo-FleQ) and facilitate the production of an antifungal weapon (HSAF) by the OH11 strain, may be secreted via the FT3SS, it is speculated that the expression of Xanthomonas oryzae FliE (Xo-FliE) would fully open the export channel of the FT3SS through interactions of Xo-FliE with FliP and FliR, allowing the positive regulators to exit the cell and suppressing HSAF production.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of the FliP5-FliQ4-FliR1 complex is formed with a helical array of subunits, and so FliE, which is the first export substrate transported by the fT3SS [31], can directly assemble on FliP and FliR to form the most proximal part of the rod structure with a helical symmetry [8,9]. Interactions of FliE with FliP and FliR fully open the exit gate of the polypeptide channel, allowing other axial proteins to diffuse down the central channel of the growing structure and assemble at the distal end [32]. So, if FliE is missing in the basal body, the fT3SS is unable to transport other axial proteins out of the cytoplasm [17,31].…”
Section: Flip Fliq and Flir Form A Polypeptide Channel Inside The Ms-...mentioning
confidence: 99%
“…The FliP 5 -FliQ 4 -FliR 1 complex has a helical arrangement of subunits similar to the rod ( Figure 3 ), so FliE, which is the first export substrate transported by the fT3SS ( Minamino and Macnab, 1999 ; Minamino et al, 2000 ), can directly assemble at the distal end of the FliP 5 -FliQ 4 -FliR 1 complex to form the most proximal part of the rod. Interactions between FliE and FliF not only firmly connect the rod with the MS ring but also open the exit gate of the polypeptide channel through conformational changes of FliP and FliR ( Hendriksen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%